Unmanipulated haploidentical haematopoietic stem cell transplantation for children with severe aplastic anaemia. (5th June 2016) - Zhu, Hua; Luo, Rong Mu; Luan, Zuo; Lee, Vincent; Zhu, Yi Ping; Luo, Cheng Juan; Tang, Xiang Feng; Si, Ying Jian; Chen, Jing
Summary: Haploidentical haematopoietic stem cell transplantation (haplo‐HSCT) used to be a third‐line treatment option for childhood severe aplastic anaemia (SAA). We conducted this retrospective study of 36 children (38 transplants) who received haplo‐HSCT from human leucocyte antigen (HLA)‐mismatched related donors between July 2002 and November 2013 at five HSCT centres in China, including 17 cases that were 5/6 HLA matched (Group 1) and 21 that were 4/6 or 3/6 HLA matched (Group 2). Although patients in Group 2 had a higher incidence of grade II‐IV acute graft‐versus‐host disease (57·9% vs. 5·9%, P  = 0·001), they had similar rates of graft failure (5·3% vs. 5·9%, P  = 0·742) and overall survival (80·8% vs. 93·8%, P  = 0·234) as Group 1. Unmanipulated haplo‐HSCT is an effective treatment for SAA children with satisfactory outcome of this cohort, especially in the 5/6 HLA‐matched group. For patients in critical situations, such as unresponsive to immunosuppressive therapy, refractory infection and failing first HSCT, to bring forward the timing of haplo‐HSCT is a feasible salvage strategy with better and faster donor accessibility.